Analysis of suitability and carrying capacity of mangrove ecosystem for ecotourism in Lembar Village, West Lombok District, Indonesia - Sukuryadi Abdillah; NUDDIN HARAHAB; MIMIT PRIMYASTANTO; BAMBANG SEMEDI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Sukuryadi, Harahab N, Primyastanto M, Semedi B. 2020. Analysis of suitability and carrying capacity of mangrove ecosystem for ecotourism in Lembar Village, West Lombok District, Indonesia. Biodiversitas 21: 596-604. Mangrove ecosystems in Lembar Village, West Lombok District, Indonesia has high ecological role and economic potentials, and have been as a pilot area for mangrove conservation and rehabilitation activities. In 2015 the area was developed into a mangrove ecotourism area as a form of utilization to obtain ecological and economic sustainability for the local community. The purpose of this study was to determine the suitability and carrying capacity of the mangroves area for the development of mangrove ecotourism. Data collection was conducted using field surveys and direct observation. Data collected were then analyzed to calculate ecotourism suitability index and carrying capacity of the area. The results of data analysis showed that mangrove ecosystem area in Lembar Village is categorized as suitable to be developed as mangrove ecotourism at three stations with value of ecotourism suitability index of 77.78%, while at two stations are categorized conditionally suitable with ecotourism suitability index of 42.22%. Carrying capacity of the area is 2337 people/day with tourist attractions consisting of mangrove tracking (33 people/day), fishing (137 people/day), picnic (1620 people/day), camping ground (542 people/day) and bird watching (6 people/day). Utilization of area based on suitability and carrying capacity is needed to maintain the sustainability of mangrove ecosystems and the economy of coastal communities.